L’assurance-crédit - Brunet, Richard (Assurances, 1982)
Credit insurance is the speciality of a few insurers, mostly American. We are therefore pleased to receive this text by Mr. Richard Brunet, which explains the subject in some detail. It is rather strange that credit insurance is little known in Canada, in spite of several large losses. This is perhaps because the coverage is rather complicated, or perhaps because the insured does not always want to provide the detailed information required by underwriters, or possibly the exclusions are considered to be unacceptable. At any rate, at a time when bankruptcies are numerous and costly, Mr. Brunet's study will make the reader aware of the exact nature of the coverage.